Long-term athlete development: seasonal and longitudinal fitness changes in female university rugby players - Falk Neto, J. H.; Parent, E. C.; Kennedy, M. D. (The Journal of Strength and Conditioning Research, 2021)
The Long-Term Athlete Development model is used by organizations to determine the expected improvements from athletes at different stages of their careers. For female rugby athletes, university sports should provide continued support for athlete development during the Training to Perform stage (18-21 years old). However, little evidence exists for longitudinal changes across years of participation in university sports in this group. The purpose of this study was to assess changes in anthropometric and fitness characteristics in female university rugby players across different seasons. Seventeen players were divided into forwards (n = 9, 21.1 ± 2.6 years) and backs (n = 8, 19.62 ± 0.9 years) and assessed across 5 points over 3 years: preseason 1, postseason 1, preseason 2, postseason 2, and preseason 3. Anthropometric (height, body mass, and body mass index) and performance measurements (grip strength, flexibility, trunk muscular endurance, upper-body muscular endurance, 40-m sprint, vertical jump, and 20-m shuttle run) were collected. Vo2max was higher at preseason 2 compared with postseason 1 (p = 0.02), postseason 2 (p = 0.01), and preseason 3 (p = 0.015), and trunk muscular endurance was higher at preseason 3 (p = 0.02). Performance in the first 5 m of the sprint test decreased at postseason 1 (p = 0.018) and preseason 2 (p = 0.016) when compared with preseason 1. The results indicate that these female athletes did not improve their fitness across the Training to Perform stage when participating in university sports. These female rugby players likely developed their fitness at earlier stages and, at this stage, already possessed well-developed fitness levels, which were merely maintained throughout years.